Feasibility of ablative stereotactic body radiation therapy of pancreas cancer patients on a 1.5 Tesla magnetic resonance-linac system using abdominal compression - Tyagi, Neelam; Liang, Jiayi; Burleson, Sarah; Subashi, Ergys; Godoy Scripes, Paola; Tringale, Kathryn R.; Romesser, Paul B.; Reyngold, Marsha; Crane, Christopher H. (Physics and imaging in radiation oncology, 2021)
Stereotactic body radiation therapy delivered using MR-guided radiotherapy (MRgRT) and automatic breathold gating has shown to improve overall survival for locally advanced pancreatic cancer (LAPC) patients. The goal of our study was to evaluate feasibility of treating LAPC patients using abdominal compression (AC) and impact of potential intrafraction motion on planned dose on a 1.5T MR-linac. Ten LAPC patients were treated with MRgRT to 50 Gy in 5 fractions with daily online plan adaptation and AC. Three orthogonal plane cine MRI were acquired to assess stability of AC pressure in minimizing tumor motion. Three sets of T2w MR scans, pre-treatment (MRIpre), verification (MRIver) and post-treatment (MRIpost) MRI, were acquired for every fraction. A total of 150 MRIs and doses were evaluated. Impact of intrafraction organ motion was evaluated by propagating pre-treatment plan and structures to MRIver and MRIpost, editing contours and recalculating doses. Gross tumor volume (GTV) coverage and organs-at-risk (OARs) doses were evaluated on MRIver and MRIpost. Median total treatment time was 75.5 (49–132) minutes. Median tumor motion in AC for all fractions was 1.7 (0.7–7), 2.1 (0.6–6.3) and 4.1 (1.4–10.0) mm in anterior-posterior, left–right and superior-inferior direction. Median GTV V50Gy was 78.7%. Median D5cm3 stomach_duodenum was 24.2 (18.4–29.3) Gy on MRIver and 24.2 (18.3–30.5) Gy on MRIpost. Median D5cm3 small bowel was 24.3 (18.2–32.8) Gy on MRIver and 24.4 (16.0–33.6) Gy on MRIpost. Dose-volume constraints for OARs were exceeded for some fractions on MRIver and MRIpost. Longer follow up is needed to see the dosimetric impact of intrafraction motion on gastrointestinal toxicity.